Dykha O.V., Bilyk A.P., Petruk R.V. A test of optimum content of the special additive is to industrial oil. - Диха, О.В.; Білик, А.П.; Петрук, Р.В. (Problems of Tribology, 2014)
Developed theory of method of tests of lubricating materials for research of wearproof properties on basis four balls chart of tests. In basis of method dimensionless conformity to law is fixed wear from the base factor of contact pressure. As a result of decision of reverse wear- contact task the got dependences are for the calculation of parameters of model of wear from experimental data. Conducted tests on a chart four - ball pyramid of industrial oil of I-40 with additions of the antiwear special additive of DF. An additive was added different concentration. The results of realization of the offered method of treatment of results of tests allowed to set the optimum value of content of additive after the criterion of minimization of wear.